2017
DOI: 10.1111/mec.14179
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, broad‐scale gene expression evolution in experimentally harvested fish populations

Abstract: Gene expression changes potentially play an important role in adaptive evolution under human-induced selection pressures, but this has been challenging to demonstrate in natural populations. Fishing exhibits strong selection pressure against large body size, thus potentially inducing evolutionary changes in life history and other traits that may be slowly reversible once fishing ceases. However, there is a lack of convincing examples regarding the speed and magnitude of fisheries-induced evolution, and thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 74 publications
3
63
0
Order By: Relevance
“…Differential responses to thiamine deficiency among families comprise 1,446 putatively adaptive genes. The large number of putatively adaptive genes with expression patterns that may be subject to selection is consistent with previous findings describing major roles for regulatory changes in adaptation (Jones et al, ; Schoville, Barreto, Moy, Wolff, & Burton, ; Uusi‐Heikkilä et al, ). A total of 812 genes were significantly upregulated in untreated individuals from high‐survival families (Figure a,c).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Differential responses to thiamine deficiency among families comprise 1,446 putatively adaptive genes. The large number of putatively adaptive genes with expression patterns that may be subject to selection is consistent with previous findings describing major roles for regulatory changes in adaptation (Jones et al, ; Schoville, Barreto, Moy, Wolff, & Burton, ; Uusi‐Heikkilä et al, ). A total of 812 genes were significantly upregulated in untreated individuals from high‐survival families (Figure a,c).…”
Section: Discussionsupporting
confidence: 89%
“…One alternative to these approaches is experimental transcriptomics. By carefully designing treatments, rearing F 1 offspring in a common environment and deeply sequencing mRNA, it is possible to uncover an adaptive, genetic response to selection (Christie, Marine, Fox, French, & Blouin, ; Passow et al, ; Uusi‐Heikkilä, Sävilammi, Leder, Arlinghaus, & Primmer, ). Coupling family‐level replication and formal survival analyses allows for the disentanglement of treatment effects, required for understanding how individuals plastically respond to environmental stressors, and among‐family variation in survival and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Although laboratory selection experiments (e.g. Conover & Munch, ; Edley & Law, ; Uusi‐Heikkilä, Savilammi, Leder, Arlinghaus, & Primmer, ; Uusi‐Heikkilä et al, ) and theoretical modelling (e.g. Dunlop, Heino, & Dieckmann, ; Ernande, Dieckmann, & Heino, ; Stokes et al, ) make a strong case for the existence of FIE, there are considerably more reviews of FIE (more than ten; cf.…”
Section: Communication Of Fie Science To Decision‐makersmentioning
confidence: 99%
“…There is considerable evidence that fisheries-like selection in a laboratory setting can effect genetic change (e.g. Conover & Munch, 2002;Uusi-Heikkilä et al, 2017;Uusi-Heikkilä et al, 2015), but empirical evidence of such change in wild populations is, at best, not nearly as strong as it is for HIE resulting from hatcheries and aquaculture.…”
Section: Are There Clear and Unambiguous Examples Of These Issues?mentioning
confidence: 99%
“…In earlier studies, the zebrafish selection lines have been found to differ phenotypically in reproductive allocation (defined as the amount of energy allocated to reproduction; Lester, Shuter, & Abrams, ), post‐maturation growth and adult body size (Uusi‐Heikkilä et al, ). Moreover, the selection lines differ genetically, in gene expression profiles and in personality traits (Sbragaglia, Alós, et al, ; Uusi‐Heikkilä, Savilammi, Leder, Arlinghaus, & Primmer, ; Uusi‐Heikkilä et al, ). In particular, the line in which large individuals were harvested (simulated trawl‐like selectivity patterns or harvest regulations mimicking minimum‐landing sizes) evolved a smaller body length, earlier age at maturity, higher relative fecundity and a smaller maximum length compared to the control, suggesting evolution towards a fast life history (Uusi‐Heikkilä et al, ).…”
Section: Introductionmentioning
confidence: 99%